Development of alternative herbals remedy for gastric cancer based on transcriptomic analysis of immune infiltration and ferroptosis - Li, Mingyue; Tao, Jie; Qian, Rui; Jiang, Feng; Song, Yinzhi; Zeng, Zhicong; Cai, Changlong (Frontiers in Genetics, 2023)
Objective:To screening out potential herbal medicines and herbal ingredients for candidates of treating gastric cancer based on transcriptomic analysis of immune infiltration and ferroptosis. Methods: Gene expression profiles of gastric tumor tissue and normal tissue samples were obtained from GEO database, and immune cell infiltration condition and differential expressed genes of ferroptosis were analyzed on the samples. Through protein-protein interaction (PPI) and enrichment analysis, the key genes were screened out, and based on the key genes, the potential herbal medicine and herbal ingredients of gastric cancer were predicted and validated using molecular docking. Results: Immune cell infiltration analysis revealed that high levels of infiltration of activating CD4 memory T cells, monocytes, M0 macrophages were present in gastric tumor tissues, while plasma cells and resting mast cells had higher levels of infiltration in the paraneoplastic tissues. Differential gene expression analysis identified 1012 up-regulated genes and 880 down-regulated genes, of which 84 immune related differentially expressed genes such as CTSB, PGF and PLAU and 10 ferroptosis related differentially expressed genes such as HSF1, NOX4 and NF2 were highly expressed in gastric cancer tissues. The results of enrichment analysis showed that they mainly involve 343 types of biological processes such as extracellular matrix organization, extracellular structural organization; 37 types of cellular components such as complexes of collagen trimer, basement membrane; 35 types of molecular functions such as signal receptor activator activity, receptor ligand activity; and 19 regulatory pathways such as cytokine-cytokine receptor interactions and retinol metabolism, etc. Finally, two key genes, TLR4 and KRAS, were selected as the key genes and based on that 12 herbal medicines such as Radix Salviae liguliobae, Rhizoma Coptidis, Rhizoma Polygoni cuspidati and 27 herbal ingredients such as resveratrol, salvianolic acid b were predicted. Molecular docking results showed that KRAS bound strongly to coumarin and honokiol, while TLR4 could bind tightly to resveratrol, curcumin, salvianolic acid b, shikonin. Conclusion:Herbal medicines such as Salviae liguliobae, Rhizoma Coptidis, Rhizoma Polygoni cuspidati and herbal ingredients such as resveratrol, curcumin, salvianolic acid b may provide research directions and alternative therapies for immunomodulation of TME and ferroptosis of tumour cells in gastric cancer.